Efficacy of Participation-Focused Therapy on Performance of Physical Activity Participation Goals and Habitual Physical Activity in Children With Cerebral Palsy: A Randomized Controlled Trial - Reedman, S.; Boyd, Roslyn; Trost, S.; Elliott, Catherine; Sakzewski, L. (W.B. Saunders Co., 2019)
Objective: To determine the efficacy of a participation-focused therapy (ParticiPAte CP) on leisure-time physical activity goal performance and satisfaction and habitual physical activity (HPA) in children with CP. Design: Randomized waitlist-controlled trial. Setting: Home and community. Participants: Children classified at Gross Motor Function Classification System (GMFCS) levels I-III were recruited (n=37; 18 males; mean age ± SD, 10.0±1.4y) from a population-based register. Interventions: Participants were randomized to ParticiPAte CP (an 8-wk goal-directed, individualized, participation-focused therapy delivered by a physical therapist) or waitlist usual care. Main Outcome Measures: The primary outcome was Canadian Occupational Performance Measure. Accelerometers were worn for objective measurement of HPA (min/d moderate-to-vigorous physical activity [MVPA], sedentary time). Barriers to participation, community participation, and quality-of-life outcomes were also collected. Data were analyzed by intention-to-treat using generalized estimating equations. Results: ParticiPAte CP led to significant improvements in goal performance (mean difference [MD]=3.58; 95% confidence interval [95% CI], 2.19-4.97; P<.001), satisfaction (MD=1.87; 95% CI, 0.37-3.36, P=.014), and barriers to participation (MD=26.39; 95% CI, 6.13-46.67; P=.011) compared with usual care at 8 weeks. There were no between-group differences on minutes per day of MVPA at 8 weeks (MD=1.17; 95% CI, -13.27 to 15.61; P=.874). There was a significant difference in response to intervention between participants who were versus were not meeting HPA guidelines at baseline (MD=15.85; 95% CI, 3.80-27.89; P<.0061). After ParticiPAte CP, low active participants had increased average MVPA by 5.98±12.16 minutes per day. Conclusion: ParticiPAte CP was effective at increasing perceived performance of leisure-time physical activity goals in children with CP GMFCS I-III by reducing modifiable barriers to participation. This did not translate into change in HPA on average; however, low active children may have a clinically meaningful response.